Sistem Pemetaan Sinyal Tiga Dimensi Wi-Fi Berbasis Android - Elviawan Riyani Septima Hardiyanto; Jihan Aulia Sashiomarda; Andia Enggar Mayasari; Ianatush Sholihah; Yusuf Sulistyo Nugroho (Universitas Merdeka Malang, 2025)
The demand for stable Wi-Fi access continues to rise, but changes in room layouts often lead to degraded signal quality, necessitating efficient detection solutions. This research aims to develop an Android-based application for three-dimensional (3D) Wi-Fi signal mapping, leveraging smartphones as affordable devices to identify problematic areas. The software development employed the Agile methodology, with key features including 3D grid clustering, color-based visualization according to signal strength (-30 dBm to -100 dBm), and multi-SSID support. Evaluation was conducted in two stages: functional testing using the Black Box Testing method, and usability testing using the System Usability Scale (SUS) instrument. Evaluation results showed a usability score of 77.22 (categorized as